Upaya Meningkatkan Kemampuan Belajar Siswa pada Materi Iman Kepada Hari Akhir Melalui Model Think Pair Share (TPS) dan Media Audio Visual pada Mata Pelajaran PAI - Saipul Bahroni; Elfa Frinadra; Eny Lutfi (STIKes Ibnu Sina Ajibarang, 2023)
This research is a classroom action research (CAR) that aims to improve student learning outcomes in Islamic Religious Education subjects, especially in the competency of Faith in the Last Day, through the application of the Think Pair Share (TPS) learning model combined with audio-visual media. The main problem raised in this study is the low student learning outcomes due to the lack of variation in learning models and media used by teachers. This research was conducted in two cycles, each involving the stages of planning, implementing actions, observation, and reflection. In the first cycle, the learning process was carried out by providing materials, pair discussions, and showing videos about the afterlife. Student learning outcomes showed an increase, but still had not achieved maximum completion. In the second cycle, improvements were made by using more appropriate learning videos and implementing more intensive sharing between groups. As a result, the average value increased from 69.2 in cycle I to 81.6 in cycle II, and learning completion increased from 60% to 92%. The results of the study showed that the application of the Think Pair Share model with the help of audio-visual media can significantly improve student learning outcomes.